1974
DOI: 10.1103/physreva.10.1568
|View full text |Cite
|
Sign up to set email alerts
|

Multiple scattering of heavy ions of keV energies transmitted through thin films

Abstract: This paper describes experimental studies of the multiple scattering of a number of different ions with 1 & Z 1 & 18 and 500 keV incident energy, transmitted through thin films of Se, Pd, Ag, Te, Ta20&, and Bi, and foils consisting of a mixture of C and Au atoms. We found that the targets fell into two groups with respect to structure. The first group, in which the targets were amorphous or had very small crystallites, showed multiple-scattering distributions of heavy ions, in agreement with current 0 theory. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
1

Year Published

1978
1978
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(8 citation statements)
references
References 16 publications
2
4
1
Order By: Relevance
“…We have confirmed the discrepancies between theoretical angular distribution for amorphous targets and measured angular distribution for a polycrystalline gold target observed at higher energies [3].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…We have confirmed the discrepancies between theoretical angular distribution for amorphous targets and measured angular distribution for a polycrystalline gold target observed at higher energies [3].…”
Section: Discussionsupporting
confidence: 86%
“…The results confirm previous experiments at higher energies [3] showing deviations from the theoretical predictions based on the standard multiple scattering theory [1,2]. In order to prove that the effect of crystal structure is one of the main causes of these deviations we have performed numerical simulations which take into account the simultaneous interaction of the proton with nearest neighbours situated in the positions corresponding to a f.c.c.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…As our clusters are substantially larger than theirs and have a much higher Z 1 , and as our energies are closer to the maximum in S n than theirs, we should have seen very substantial non-linear effects in S n . From our lack of any such evidence and from the theoretical [11] and experimental [15] evidence for such effects only to exist at very low energies and having the opposite sign of what was found by He et al, we think that their interpretation is not correct. Their results can be explained, in agreement with the others, by the observation of a non-linear relation between deposited energy density and ion beam mixing, without a non-linearity in S n .…”
Section: A) Experiments and Simulationcontrasting
confidence: 55%
“…The authors of [241] reported about Z , oscillations of the angular distribution half-widths. At scattering on polycrystal targets having grain sizes exceeding 10 nm the experimental angular half-widths reach sometimes only 25% of the theoretical ones [243]. That was assigned to the channeling effect.…”
Section: Multiple Scatteringmentioning
confidence: 84%